The Importance Of Rate And Time Dependence On Conversion Of NOx In The Cleaning Of NOx In Exhaust Gases Using Ozone. - Patah, Abir Abdul; Fernando, W.J.N.; Mohamed, Abdul Rahman; Bakar, M Zailani Abu (2005)
The reactions involved in the ozonation of NOx present in the exhaust gases are discussed. The equations of reaction rate te fonnulated and the kinetic model anatysis is presented to describe the reaction rate of removal NOx from simulated exhaust gases.